La RVAE au milieu du gué : questions en suspens et perspectives entre contexte national et européen - Gilles Pinte (Université de Provence, 2013)
The process and devices of accreditation of prior experiential learning (APEL) have been developped continually over the past thirty years. They have, according to the country, allowed candidates without the necessary academic pre-requisites to access various levels of training and to obtain, partially or totally, a diploma or professional qualifications thanks to their professional experience. The development of APEL has not been without hurdles, but over time the criticism and doubt expressed in regards to the certification procedure have decreased.